Is consumer confidence an indicator of JSE performance? - Kamini Solanki; Yudhvir Seetharam (Contemporary Economics, 2014)
While most studies examine the impact of business confidence on market performance, we instead focus on the consumer because consumer spending habits are a natural extension of trading activity on the equity market. This particular study examines investor sentiment as measured by the Consumer Confidence Index in South Africa and its effect on the Johannesburg Stock Exchange (JSE). We employ Granger causality tests to investigate the relationship across time between the Consumer Confidence Index and market performance. The results show weak evidence of a contemporaneous relationship; however, significant evidence of a Granger caused relationship is apparent. Further, changes in investor sentiment Granger-cause changes in the two indices used, generally with a lag of 9 and 12 months, but not vice versa. Thus, we find that Consumer Confidence leads JSE performance during our sample period. Our research provides evidence contradicting the common perception of consumer confidence lagging market performance, particularly in the South African context.
Keywords: C01; C58; D53; D84; G02; 330; consumer confidence; financial markets; South Africa; behavioral finance